Effect of exercise on functional capacity in patients with advanced cancer: A meta-analysis of randomized controlled trials. (July 2022) - Avancini, Alice; Sperduti, Isabella; Borsati, Anita; Ferri, Thomas; Belluomini, Lorenzo; Insolda, Jessica; Trestini, Ilaria; Tregnago, Daniela; Schena, Federico; Bria, Emilio; Milella, Michele; Pilotto, Sara
Abstract: Purpose: To determine the impact of exercise on functional capacity, measured through the "Six minutes walking test" (6MWT) in patients with advanced cancer stage. Methods: Systematic research on PubMed, Cochrane Library, and SportDiscus was conducted. Randomized controlled trials were eligible if they examined the effect of exercise on 6MWT. Results: Overall, a total of ten trials were included in the primary analysis. Compared to the controls, the exercise intervention was associated with an increase in functional capacity (+20.86 m; CI: −5.90 to 47.72, p = 0.12) although not reaching the statistical significance. Sensitivity analysis revealed an improvement for studies proposing a supervised exercise intervention towards the statistical significance. Few adverse events were associated with exercise training, and the median withdrawals rate was 17%. Conclusions: Exercise may have a beneficial role on functional capacity in patients with advanced cancer, especially if supervised. Graphical Abstract: ga1